A new Mexican species of Oxyporus (Coleoptera: Staphylinidae: Oxyporinae) - Márquez, Juan; Asiain, Julieta (Zootaxa, 2006)
Oxyporus bautistae Márquez & Asiain, sp. nov. is described based on three female specimens collected from mushrooms of the genus Boletus in an oak forest of Oaxaca, Mexico. The new species is similar to O. lawrencei Campbell, known from Distrito Federal, Guerrero, Jalisco, Mexico, Michoacan and Morelos, Mexico, and represents the eighth Mexican species of the genus.